Towards an Evidence Base: Exploring the Impact of Community-Based Literacy Programs in Remote Indigenous Communities. Issue 2 (May 2015) - Klieve, Helen; Flückiger, Bev
THERE ARE VARIOUS COMMUNITY-BASED literacy programs in Australian communities that aim to address educational disadvantage by fostering parental engagement with their young children in literacy activities. Despite the effort and goodwill of many community members, there is little evidence of the impact of these programs on children's literacy progress, school attendance or parental engagement. This paper reports on a pilot study of parents' engagement in their child's literacy development in one remote Indigenous community. Preliminary findings from parent reports indicate elevated progress in literacy by the children in the program. Similarly, parents involved in the program report being more engaged in community leadership and in their children's literacy learning than those who are not. The study suggests aspects of the interrelationship between parent engagement and children's literacy progress that require further investigation. Broader use of the instruments developed will help to establish an evidence base and inform such an investigation.